(untitled) (Italian Journal of Public Health, 2012)
Background: the aim of the study was to assess the safety, efficacy and cost-effectiveness of negative Pressure wound therapy (nPT) for people with chronic and acute wounds. Methods: the scope and the final draft of the report have been submitted to the stakeholders (producers, payers and patients). safety issues were addressed through a systematic review of the meta-literature. efficacy was addressed through a systematic review and meta-analysis of randomized controlled trials (rcTs) comparing nPT and other standard therapies in patients with chronic or acute lesions. cost-consequence was analyzed through a systematic review of the existing studies. Results: we retrieved 19 studies, 13 of which were included in the meta-analysis. Many studies had biases that may have resulted in a better performance for nPT. nPT showed: a slightly shorter healing time (-10.4 days, p=0.001), with no heterogeneity, apart from one small study with very positive results, and 40% more patients healed (p=0.002, no heterogeneity).We identified 15 original research papers on nPT costs and cost per outcome. The costs-per-patient- treated varied from +29% to -60%, with several studies reporting savings for nPT. Conclusions: despite serious methodological flaws, the body of evidence available was sufficient to prove some clinical benefit of nPT in severe chronic and acute wound treatment. There is a need for independent and contextualized cost analyses....